The long-term prognostic significance of high-sensitive C-reactive protein to in-stent restenosis. Issue 27 (July 2018) - Zhu, Xinyi; Chen, Yuqi; Xiang, Li; You, Tao; Jiao, Yang; Xu, Weiting; Chen, Jianchang
Abstract: Background: In the current meta-analysis, we aim to assess the effect of high-sensitive C-reactive protein (hs-CRP) on in-stent restenosis (ISR) outcome in patients receiving stent implantation. Methods: Embase, PubMed, and Cochrane databases were searched through October 2016 using the keywords "high-sensitive C-reactive protein, " "in-stent restenosis." An odds ratio (OR) of on ISR endpoints among patients receiving stent implantation was calculated using random-effects models. Results: In the meta-analysis of 6 prospective observational studies, there are 1156 coronary heart disease (CHD) patients, a total of 885 stents were implanted and 194 ISR events had been followed up for 6 to 12 months; high-sensitive C-reactive protein levels are associated with the prediction of in-stent restenosis among patients receiving stent implantation. The OR of hs-CRP for ISR was 1.16 [95% confidence interval (CI), 1.01–1.30, P  < .05]. Conclusions: This meta-analysis shows that higher levels of hs-CRP are associated with an increased risk of ISR and indicate a poorer prognosis in CHD patients after stent implantation.